THU0182 Ex Vivo Functional Comparison of Baricitinib and Tofacitinib for Cytokine Signaling in Human Leukocyte Subpopulations. (15th July 2016) - McInnes, I.; Higgs, R.; Rocha, G.; Zhang, X.; Lee, J.; Wehrman, T.; Macias, W.L.; Zuckerman, S.; Taylor, P.
Abstract : Background: Baricitinib (bari) and tofacitinib (tofa) are selective JANUS kinase inhibitors (JAKi). In biochemical assays, bari exhibits greatest potency against JAK1 and JAK2, whereas that for tofa is against JAK1 and JAK3. Objectives: To determine whether differences in JAKi specificity translate to differences in cellular signal transduction in leukocyte subpopulations stimulated by cytokines, indicated by inhibition of signal transducers of activator transcription (STATs) phosphorylation. Methods: Peripheral blood mononuclear cells (PBMC) were obtained from healthy donors (n=6). Leukocyte preparations were incubated with JAKi using a 7 point dose range, 2.44–10, 000 nM, for 1 hour before cytokine stimulation. The half maximum inhibitory concentration (IC50 ) values were determined by plotting the mean fluorescence intensity of cytokine-stimulated and nonstimulated samples in phenotypically gated leukocyte subpopulations. 1 Results: IC50 values for bari and tofa were similar for interleukin-6 (IL-6) across leukocyte subsets. Differences were observed for other cytokines. The IC50 across leukocyte subpopulations stimulated with the same cytokine varied 2–3 fold per compound (Table). The most significant differences between JAKi IC50 values were for cytokines that use JAK1/3. Tofa was a more potent inhibitor of IL-2, IL-4, IL-15, and IL-21 induced STAT phosphorylation than bari. Both compounds inhibited IL-10 stimulation of pSTAT3 and IFN-α stimulation of pSTAT1, pSTAT3, and pSTAT5 similarly. Inhibition of IFN-α pSTAT3 and pSTAT5 were similar for both JAKi, although less potent in inhibiting STAT1 phosphorylation. Bari and tofa inhibited GM-CSF (JAK2) and G-CSF and IFNg signaling, with bari exhibiting a greater effect in monocytes than tofa. Conclusions: The differences in IC50 for key cytokine stimuli suggest fundamental functional differences across classes of JAKi. The potency of JAKi varied between different leukocyte subpopulations and is STAT substrate dependent. At the clinical level, therefore, these agents should not be considered biologically equivalent. A practical consequence is that determination of JAKi potency on IC50 based solely on a nongated whole blood assay would not detect differential responses of leukocyte subpopulations by JAKi. References: Krutzik, et al. Nat Methods. 2006 May;3(5): 361–368. Disclosure of Interest: I. McInnes Grant/research support from: Pfizer, UCB, Janssen, Astra Zeneca, Consultant for: Eli Lilly and Company, Pfizer, Galapagos, AbbVie, UCB, Janssen, Novartis, R. Higgs Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, G. Rocha Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, X. Zhang Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, J. Lee Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, T. Wehrman: None declared, W. Macias Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, S. Zuckerman Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, P. Taylor Grant/research support from: UCB, GlaxoSmithKline, Celgene, Consultant for: UCB, Eli Lilly and Company, Pfizer, Galapagos, Merck, GlaxoSmihKline, AbbVie, Takeda, Bristol-Myers Squibb